Technology-Supported Reminiscence Therapy for Those Living with Dementia - Aylett, Ruth; Wilson, Bruce; Lim, MeiYii; Pappa, Katerina; Aylett, Matthew; Parra-Rodriguez, Mario (Proceedings of the AAAI Symposium Series, 2024)
The AMPER application is designed to support reminiscence therapy in a domestic setting for those living with dementia through the use of an Intelligent Virtual Agent (IVA). Such agents have been shown to increase functionality, accessibility and user satisfaction. We describe the application and summarise the design process used to choose the graphical agent for the project. We briefly discuss the implications of using stereotypes or archetypes in this process.